STUDY DESKRIPTIF IMPLEMENTASI 5S DI RUANGAN ADMINISTRASI DAN PENGADAAN PERPUSTAKAAN UNIVERSITAS - Frandy Ferdinata; Siti Rahayu; Stefanus Budy Widjaja S. (Perpustakaan Universitas Surabaya, 2018)
University Surabaya is one of the major universities located in Surabaya. In everyday activities, the University always strives t manage and manage the availability of books in the library, both for students and lecturers. In order for library management to run well, Ubaya applies the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). So the purpose of this study is to describe the 5S method applied to the 2 units in the Ubaya library that is the administration and procurement department. This research is a pure descriptive type because in this research there is no implementation or design on Ubaya. The variables used in this research are 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). Source of data used to collect data on this skrispsi through observation and interview to the library. Analysis performed on the administration and procurement based on the application of Seiri, Seiton, Seiso, Seiketsu, Shitsuke. The results of the research show that the administration and procurement of the application of the 5S method has not gone well. Because it is still found in 5S activities that are not as it should be.